Evidence Gaps in Cancer Survivorship Care: A Report From the 2019 National Cancer Institute Cancer Survivorship Workshop. (23rd March 2021) - Gallicchio, Lisa; Tonorezos, Emily; de Moor, Janet S; Elena, Joanne; Farrell, Margaret; Green, Paige; Mitchell, Sandra A; Mollica, Michelle A; Perna, Frank; Saiontz, Nicole Gottlieb; Zhu, Li; Rowland, Julia; et al.
Abstract: Today, there are more than 16.9 million cancer survivors in the United States; this number is projected to grow to 22.2 million by 2030. Although much progress has been made in describing cancer survivors' needs and in improving survivorship care since the seminal 2006 Institute of Medicine report "From Cancer Patient to Cancer Survivor: Lost in Transition, " there is a need to identify evidence gaps and research priorities pertaining to cancer survivorship. Thus, in April 2019, the National Cancer Institute convened grant-funded extramural cancer survivorship researchers, representatives of professional organizations, cancer survivors, and advocates for a 1-day in-person meeting. At this meeting, and in a subsequent webinar aimed at soliciting input from the wider survivorship community, evidence gaps and ideas for next steps in the following 6 areas, identified from the 2006 Institute of Medicine report, were discussed: surveillance for recurrence and new cancers, management of long-term and late physical effects, management of long-term and late psychosocial effects, health promotion, care coordination, and financial hardship. Identified evidence gaps and next steps across the areas included the need to understand and address disparities among cancer survivors, to conduct longitudinal studies as well as longer-term (>5 years postdiagnosis) follow-up studies, to leverage existing data, and to incorporate implementation science strategies to translate findings into practice. Designing studies to address these broad evidence gaps, as well as those identified in each area, will expand our understanding of cancer survivors' diverse needs, ultimately leading to the development and delivery of more comprehensive evidence-based quality care.